Identification, phylogenetic analysis, and genome mining of the tetracycline-resistant Bacillus thuringiensis strain m401 reveal its potential for biotechnological and biocontrol applications - Alippi, Adriana Mónica (2023)
Bacillus thuringiensis is an entomopathogen belonging to the Bacillus cereus clade. We isolated a tetracycline-resistant strain called m401, recovered it from honey, and identified it as Bacillus thuringiensis sv. kumamotoensis based on the average nucleotide identity calculations (ANIb) comparison and the analysis of the gyrB gene sequences of different B. thuringiensis serovars. Sequences with homology to virulence factors [cytK, nheA, nheB, nheC, hblA, hblB, hblC, hblD, entFM, and inhA] and tetracycline resistance genes [tet(45), tet(V), and tet(M)/tet(W)/tet(O)/tet(S) family] were identified in the bacterial chromosome. The prediction of plasmid-coding regions revealed homolog sequences to the MarR and TetR/AcrR family of transcriptional regulators, toxins, and lantipeptides. The genome mining analysis revealed 12 regions of biosynthetic gene clusters responsible for synthesizing secondary metabolites. We identified biosynthetic gene clusters coding for bacteriocins, siderophores, ribosomally synthesized post-translationally modified peptide products, and non-ribosomal peptide synthetase clusters that provide evidence for the possible use of Bt m401 as a biocontrol agent. Furthermore, Bt m401 showed high inhibition against all Paenibacillus larvae genotypes tested in vitro. In conclusion, Bt m401 owns various genes involved in different biological processes, such as transductional regulators associated with antibiotic resistance, toxins, and antimicrobial peptides with potential biotechnological and biocontrol applications.